Low-cost anti-reverse polarity anode catalyst layer, membrane electrode and preparation method and application thereof
By constructing the anode catalytic layer into a proton storage layer and a hydroxide reaction layer, the proton storage capacity of transition metal oxides is used to solve the problem of catalytic layer structure failure when the anode hydrogen supply is insufficient, and low-cost and efficient anti-reverse performance is improved.
Patent Information
- Application Number
- CN202411941863.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
AI Technical Summary
During operation, existing fuel cells are prone to damage to the catalytic layer structure due to insufficient supply of anode hydrogen during operation, which in turn affects the performance and durability of the membrane electrode. The commonly used method to improve the anti-reverse ability uses expensive Ir-based catalysts, which increases the cost of raw materials.
By constructing the anode catalytic layer into a proton storage layer and a hydroxide reaction layer, the proton storage capacity of transition metal oxides such as WO3 or MoO3 is used to provide protons when the anode hydrogen supply is insufficient, avoiding carbon corrosion reactions in the catalytic layer, thereby enhancing the anti-reverse ability of the membrane electrode.
This method effectively improves the anti-reverse ability of the membrane electrode, reduces the cost of raw materials, is easy to operate, and has good economical and feasibility.
Smart Images

Figure CN119742376A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and in particular to a low-cost anti-reverse polarity anode catalyst layer, a membrane electrode, and a preparation method and application thereof. Background Art
[0002] In recent years, hydrogen fuel cells have attracted widespread attention as an efficient and environmentally friendly energy conversion device. They have the advantages of high energy density, high conversion efficiency, and no pollution to the environment, and are of great significance. However, in the commercialization process of fuel cells, durability and reliability have seriously restricted the development of fuel cells and have become the most critical issues that need to be solved.
[0003] During the operation of the fuel cell, some improper operations or conditions will cause changes in the operating state of the fuel cell, such as insufficient supply of reactants, low catalyst performance, uneven gas distribution, rapid changes in load, and start-stop operations. When the anode hydrogen supply is insufficient, the anode will not be able to produce enough protons and electrons, so the anode catalyst layer will undergo a carbon corrosion reaction to provide protons and electrons. The occurrence of the carbon corrosion reaction will cause the structure of the catalyst layer to be destroyed, the catalyst active substances will fall off and agglomerate, and the electrochemical active area will decrease. At the same time, it will also cause the porosity and hydrophilicity of the catalyst layer to change, seriously affecting the performance of the membrane electrode. In addition, the CO produced by the carbon corrosion reaction will poison the Pt catalyst and further reduce the performance of the catalyst. The large amount of heat generated when the reverse polarity occurs will form a local hot spot, which may cause membrane perforation and short circuit of the positive and negative electrodes. Therefore, improving the anti-reverse polarity ability is of great significance to improving the durability and reliability of fuel cells.
[0004] Currently, the most widely used method to improve the anti-reverse capability is to add an OER catalyst to the anode catalyst layer. For example, some technologies spray IrCl3 on the surface of the anode catalyst layer, and then perform in-situ oxidation to obtain a highly dispersed anti-reverse catalyst, thereby improving the anti-reverse capability without affecting the performance of the membrane electrode. Other technologies construct the anode catalyst layer into multiple sub-catalytic layers, and add an oxygen evolution reaction catalyst to each sub-catalytic layer. The oxygen evolution reaction catalyst is mainly an Ir-based catalyst. This invention enhances the anti-reverse capability of the membrane electrode while ensuring the initial performance of the membrane electrode. These methods all use Ir-based catalysts to improve the anti-reverse capability of the membrane electrode, and the price of Ir metal is very expensive. Adding Ir-based catalysts to the catalyst layer will significantly increase the raw material cost of the fuel cell. Summary of the invention
[0005] Based on the problem of expensive raw materials in the prior art, this application proposes a low-cost anti-reverse polarity anode catalyst layer, membrane electrode, and its preparation method and application. By constructing the anode catalyst layer into a proton storage layer and a hydrogen oxidation reaction layer, and utilizing the proton storage capacity of the transition metal oxide of the proton storage layer, protons are provided when the anode hydrogen supply is insufficient to avoid carbon corrosion reaction in the catalyst layer, which can effectively improve the anti-reverse polarity ability of the membrane electrode. The method disclosed in this application is low-cost, easy to operate, and has good economy and feasibility.
[0006] To achieve the above-mentioned objectives, the first aspect of the present application proposes a low-cost anti-reverse polarity anode catalyst layer, comprising a stacked proton storage layer and a hydrogen oxidation reaction layer, wherein the proton storage layer comprises a transition metal oxide and a perfluorosulfonic acid resin, wherein the transition metal oxide comprises at least one of WO3 and MoO3, and the hydrogen oxidation reaction layer comprises a hydrogen oxidation reaction catalyst and the perfluorosulfonic acid resin.
[0007] In some embodiments, the transition metal oxide is a nanoparticle.
[0008] In some embodiments, the transition metal oxide has a particle size of less than 200 nm.
[0009] In some embodiments, the transition metal oxide is WO3 or MoO3.
[0010] In some embodiments, in the proton storage layer, the mass ratio of the transition metal oxide to the perfluorosulfonic acid resin is 1:(0.1-1).
[0011] In some embodiments, in the hydrogen oxidation reaction layer, the mass ratio of the hydrogen oxidation reaction catalyst to the perfluorosulfonic acid resin is 1:(0.2-1).
[0012] In some embodiments, the ion exchange equivalent of the perfluorosulfonic acid resin is 700-1100 g / mol.
[0013] In some embodiments, the mass ratio of the proton storage layer to the hydrogen oxidation reaction layer is 1:(1-5).
[0014] In some embodiments, the proton storage layer has a thickness of 0.5-4 μm.
[0015] In some embodiments, the thickness of the hydrogen oxidation reaction layer is 1-10 μm.
[0016] In some embodiments, the hydrogen oxidation reaction catalyst includes an active material and a carbon support.
[0017] In some embodiments, the active material includes Pt or a Pt alloy.
[0018] In some embodiments, the carbon support includes at least one of graphitized nano-carbon powder, carbon nanotubes, carbon nanofibers, and graphene.
[0019] In some embodiments, the mass ratio of the active material to the carbon support is 1:(0.5-4).
[0020] The second aspect of the present application proposes a membrane electrode, comprising a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer, wherein the anode catalyst layer is the low-cost anti-reverse polarity anode catalyst layer described in the present application, and the proton storage layer is arranged on the proton exchange membrane away from the hydrogen oxidation reaction layer.
[0021] The third aspect of the present application provides a method for preparing a membrane electrode, comprising:
[0022] Dispersing the transition metal oxide and the perfluorosulfonic acid resin solution in a first solvent to obtain a first slurry;
[0023] Applying the first slurry on a proton exchange membrane, followed by a first drying step to obtain a proton exchange membrane containing the proton storage layer;
[0024] dispersing the hydrogenation reaction catalyst and the perfluorosulfonic acid resin solution in a second solvent to obtain a second slurry;
[0025] The second slurry is coated on the proton storage layer, followed by a second drying process, to obtain a proton exchange membrane including the hydrogen oxidation reaction layer and the proton storage layer.
[0026] In some embodiments, the first solvent and the second solvent both include a hydroalcoholic solvent.
[0027] In some embodiments, the alcohol in the hydroalcoholic solvent includes at least one of ethanol, n-propanol, and isopropanol.
[0028] In some embodiments, in the process of obtaining the first slurry and the process of obtaining the second slurry, the dispersion method includes at least one of ball milling, sand milling or ultrasound.
[0029] In some embodiments, the coating method of coating the first slurry on the proton exchange membrane and the coating method of coating the second slurry on the proton storage layer both include blade coating, slit coating or ultrasonic spray coating.
[0030] In some embodiments, the first drying and the second drying are both at a temperature of 50-90°C.
[0031] A fourth aspect of the present application provides a fuel cell, comprising the membrane electrode described in the present application or a membrane electrode prepared by the method for preparing the membrane electrode described in the present application.
[0032] In some embodiments, the fuel cell is a hydrogen fuel cell.
[0033] The low-cost anti-reverse polarity anode catalyst layer described in this application can at least bring the following beneficial effects:
[0034] 1. By constructing the anode catalyst layer into a proton storage layer and a hydrogen oxidation reaction layer, the proton storage capacity of the transition metal oxide of the proton storage layer is utilized to provide protons when the hydrogen supply at the membrane electrode anode is insufficient, thereby avoiding carbon corrosion reaction in the catalyst layer to destroy the catalyst layer, thereby effectively improving the membrane electrode's ability to resist reverse polarity.
[0035] 2. The transition metal oxides used are low-priced, avoiding the use of expensive water electrolysis catalysts, which can reduce the cost of raw materials while improving the anti-reverse polarity performance of the membrane electrode.
[0036] 3. It can be prepared through a two-step simple coating process.
[0037] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.
[0039] in:
[0040] Figure 1 This is a flow chart of a method for preparing a membrane electrode according to an exemplary embodiment of the present application.
[0041] Figure 2 A schematic diagram of the anti-reverse polarity principle of a low-cost anti-reverse polarity anode catalyst layer is shown as an exemplary embodiment of the present application.
[0042] Figure 3 Polarization curves of membrane electrodes prepared in Example 1 and Comparative Examples 1-3.
[0043] Figure 4 The voltage curves of the membrane electrodes prepared in Example 1 and Comparative Examples 1-3 when lacking hydrogen. DETAILED DESCRIPTION
[0044] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0045] In this application, the disclosure of numerical ranges includes all values within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.
[0046] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0047] The term "and / or", when used in a list of two or more items, means that any of the listed items can be used alone or in combination with any one or more of the listed items. For example, the expression "A and / or B" is intended to mean A or B or A and B, that is, only A, only B, or a combination of A and B.
[0048] <Low-cost anti-reverse polarity anode catalyst layer>
[0049] The low-cost anti-reverse polarity anode catalyst layer of this embodiment includes a proton storage layer and a hydrogen oxidation reaction layer which are stacked, the proton storage layer includes a transition metal oxide and a perfluorosulfonic acid resin, the transition metal oxide includes at least one of WO3 and MoO3, the hydrogen oxidation reaction layer includes a hydrogen oxidation reaction catalyst and the perfluorosulfonic acid resin.
[0050] like Figure 2 As shown, the principle of the low-cost anti-reverse polarity anode catalyst layer anti-reverse polarity of the embodiment of the present application is:
[0051] The low-cost anti-reverse anode catalyst layer is a double-layer structure, with the proton storage layer close to the proton exchange membrane and the hydrogen oxidation reaction layer away from the proton exchange membrane. Under normal conditions, the hydrogen oxidation reaction catalyst undergoes H2 oxidation to generate protons and electrons. y , M is W or Mo, y = 3) combines with protons and electrons to produce metal acids (H x MO y , x is the number of protons stored in the transition metal oxide, y = 3); in the absence of hydrogen, the metal acid is ionized to produce protons, electrons and transition metal oxides, and the protons are transferred to the cathode through the proton exchange membrane to avoid carbon corrosion reaction in the catalyst layer.
[0052] It should be noted that, in the embodiment of the present application, the low-cost anti-reverse polarity anode catalyst layer is set as a two-layer structure of a proton storage layer and a hydrogen oxidation reaction layer. Compared with concentrating all materials of the proton storage layer and the hydrogen oxidation reaction layer in one material layer (single-layer structure), it has the following advantages: the hydrogen oxidation reaction catalyst needs to have a suitable three-phase interface to work, that is, it needs to be coated with a suitable perfluorosulfonic acid resin on the hydrogen oxidation catalyst. On the one hand, it ensures that the reactant H2 can contact with the hydrogen oxidation catalyst to undergo an oxidation reaction, and on the other hand, it ensures that the product H+ and can be transferred to the proton exchange membrane through the perfluorosulfonic acid resin; while the H stored and released by the transition metal oxide + It needs to be transferred through perfluorosulfonic acid resin, so perfluorosulfonic acid resin also needs to be properly coated. The amount of perfluorosulfonic acid resin required for the hydrogenation reaction catalyst and the transition metal oxide is different. If the two substances are mixed together (single-layer structure), the perfluorosulfonic acid resin required for the two substances cannot be regulated separately. However, by setting the hydrogenation reaction catalyst and the transition metal oxide as a double-layer structure, the perfluorosulfonic acid resin required for both can be independently regulated, thereby improving the utilization efficiency.
[0053] In some embodiments, the transition metal oxide is a nanoparticle.
[0054] In some embodiments, the particle size of the transition metal oxide is less than 200 nm, including but not limited to less than 180 nm, less than 150 nm, less than 125 nm, less than 100 nm, less than 80 nm, less than 50 nm, less than 25 nm or less than 10 nm.
[0055] As a preferred example, the transition metal oxide is WO3 or MoO3, more preferably WO3.
[0056] In the embodiment of the present application, the perfluorosulfonic acid resin in the proton storage layer is the same as the perfluorosulfonic acid resin in the hydrogen oxidation reaction layer.
[0057] In some embodiments, in the proton storage layer, the mass ratio of the transition metal oxide to the perfluorosulfonic acid resin is 1:(0.1-1), including but not limited to 1:0.1, 1:0.25, 1:0.5 or 1:0.75, etc. The mass ratio of the transition metal oxide to the perfluorosulfonic acid resin is within the above range to ensure that the transition metal oxide is properly coated by the perfluorosulfonic acid resin, which is beneficial to the transmission of protons and electrons; if it is lower than 1:1, the transition metal oxide may be completely wrapped by the perfluorosulfonic acid resin, making it difficult to transmit electrons; if it is greater than 1:0.1, the area of the transition metal oxide coated by the perfluorosulfonic acid resin is too small, and there are fewer proton transmission channels, which is not conducive to the storage and release of protons.
[0058] In some embodiments, in the hydrogen oxidation reaction layer, the mass ratio of the hydrogen oxidation reaction catalyst to the perfluorosulfonic acid resin is 1:(0.2-1), including but not limited to 1:0.2, 1:0.3, 1:0.5, 1:0.75 or 1:0.9, etc.
[0059] In some embodiments, the ion exchange equivalent of the perfluorosulfonic acid resin is 700-1100 g / mol, including but not limited to 750 g / mol, 800 g / mol, 850 g / mol, 900 g / mol, 950 g / mol, 1000 g / mol or 1050 g / mol.
[0060] In some embodiments, the mass ratio of the proton storage layer to the hydrogen oxidation reaction layer is 1:(1-5), including but not limited to 1:1, 1:2, 1:3, 1:4 or 1:5, etc.
[0061] In some embodiments, the proton storage layer has a thickness of 0.5-4 μm, including but not limited to 0.5 μm, 1 μm, 2 μm, 3 μm or 4 μm.
[0062] In some embodiments, the thickness of the hydrogen oxidation reaction layer is 1-10 μm, including but not limited to 1 μm, 3 μm, 5 μm, 8 μm or 10 μm, etc.
[0063] In some embodiments, the hydrogen oxidation reaction catalyst includes an active material and a carbon support.
[0064] In some embodiments, the active material includes but is not limited to Pt or Pt alloy.
[0065] Exemplarily, the Pt alloy includes, but is not limited to, at least one of Pt-Co, Pt-Ru, Pt-Ni, Pt-Pd, and the like.
[0066] In some embodiments, the carbon carrier includes but is not limited to at least one of graphitized nano-carbon powder, carbon nanotubes, carbon nanofibers, graphene, and the like.
[0067] In some embodiments, the mass ratio of the active substance to the carbon carrier is 1:(0.5-4), including but not limited to 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3 or 1:3.5, etc.
[0068] As an optional example, the mass ratio of the transition metal oxide to the hydrogen oxidation reaction catalyst is 1:(1-3), including but not limited to 1:1, 1:1.5, 1:2 or 1:2.5, etc.
[0069] The low-cost anti-reverse polarity anode catalyst layer of the embodiment of the present application can at least bring the following beneficial effects:
[0070] 1. By constructing the anode catalyst layer into a proton storage layer and a hydrogen oxidation reaction layer, the proton storage capacity of the transition metal oxide of the proton storage layer is utilized to provide protons when the hydrogen supply at the membrane electrode anode is insufficient, thereby avoiding carbon corrosion reaction in the catalyst layer to destroy the catalyst layer, thereby effectively improving the membrane electrode's ability to resist reverse polarity.
[0071] 2. The transition metal oxides used are low-priced, avoiding the use of expensive water electrolysis catalysts, which can reduce the cost of raw materials while improving the anti-reverse polarity performance of the membrane electrode.
[0072] 3. It can be prepared through a two-step simple coating process.
[0073] <Membrane Electrode>
[0074] The membrane electrode of the embodiment of the present application includes a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer. The anode catalyst layer is a low-cost anti-reverse polarity anode catalyst layer of the embodiment of the present application. The proton storage layer is arranged on the proton exchange membrane away from the hydrogen oxidation reaction layer.
[0075] It should be noted that in the embodiments of the present application, if the hydrogen oxidation reaction layer is close to or in close contact with the proton exchange membrane, the protons generated by the proton storage layer must first pass through the hydrogen oxidation reaction layer and then be conducted to the proton exchange membrane. The proton conduction path will become longer and the proton transfer resistance will become greater, so the reversal time will become worse.
[0076] It should also be noted that in the embodiments of the present application, there is no limitation on the specific selection of proton exchange membrane, cathode catalyst layer, etc. They can be any proton exchange membrane, cathode catalyst layer, etc. that can be used in fuel cells, especially hydrogen fuel cells in the art.
[0077] Exemplarily, the proton exchange membrane includes, but is not limited to, a perfluorosulfonic acid membrane, a non-perfluorinated membrane, a non-fluorinated membrane or a composite membrane.
[0078] Exemplarily, the cathode catalyst layer includes, but is not limited to, a platinum catalyst layer, a platinum alloy catalyst layer, or a non-platinum-based catalyst layer.
[0079] In some embodiments, the membrane electrode further includes an anode gas diffusion layer, a cathode gas diffusion layer, a frame, and the like.
[0080] <Method for preparing membrane electrode>
[0081] The method for preparing the membrane electrode of the embodiment of the present application can be used to prepare the membrane electrode of the embodiment of the present application.
[0082] It should be noted that the method for preparing the membrane electrode of the embodiment of the present application forms a low-cost anti-reverse polarity anode catalyst layer of the embodiment of the present application during the preparation process of the membrane electrode. Therefore, it can also be regarded as the method for preparing the low-cost anti-reverse polarity anode catalyst layer of the embodiment of the present application.
[0083] The method for preparing the membrane electrode of the embodiment of the present application comprises the following steps:
[0084] S101, dispersing the transition metal oxide and the perfluorosulfonic acid resin solution in a first solvent to obtain a first slurry.
[0085] In some embodiments, the perfluorosulfonic acid resin solution is a dispersion of perfluorosulfonic acid resin in one or more solvents including water, ethanol, n-propanol or isopropanol, wherein the solid content is 5-30wt%, including but not limited to 10wt%, 15wt% or 20wt%, etc.
[0086] In some embodiments, the mass ratio of the transition metal oxide to the perfluorosulfonic acid resin is 1:(0.1-1), including but not limited to 1:0.1, 1:0.25, 1:0.5 or 1:0.75, etc.
[0087] In some embodiments, the first solvent includes a hydroalcoholic solvent (ie, a mixed solvent of water and alcohol).
[0088] Exemplarily, the mass ratio of water to alcohol in the hydroalcohol solvent is 1:(0.5-6), including but not limited to 1:0.5, 1:1, 1:2, 1:4 or 1:6, etc.
[0089] Exemplarily, the alcohol includes, but is not limited to, at least one of ethanol, n-propanol, and isopropanol.
[0090] In some embodiments, the dispersion method of dispersing the transition metal oxide and the perfluorosulfonic acid resin solution in the first solvent includes but is not limited to at least one of ball milling, sand milling or ultrasound.
[0091] In some embodiments, the solid content of the first slurry is 1-25 wt %, including but not limited to 5 wt %, 12 wt % or 20 wt %, etc.
[0092] S102, coating the first slurry on a proton exchange membrane, and then performing a first drying to obtain a proton exchange membrane containing the proton storage layer.
[0093] In some embodiments, the coating method of coating the first slurry on the proton exchange membrane includes but is not limited to at least one of blade coating, slit coating or ultrasonic spray coating.
[0094] In some embodiments, the first slurry is applied on the proton exchange membrane by knife coating or slit coating to a coating thickness of 10-60 μm, and the spraying speed of ultrasonic spray coating is 0.5-4 mL / min.
[0095] Exemplarily, the wet thickness includes but is not limited to 20 μm, 35 μm or 55 μm, etc., and the spraying speed of ultrasonic spraying includes but is not limited to 1 mL / min, 2 mL / min or 3 mL / min, etc.
[0096] In some embodiments, the first drying temperature is 50-90°C, including but not limited to 55°C, 65°C, 75°C or 85°C.
[0097] S103, dispersing the hydrogenation reaction catalyst and the perfluorosulfonic acid resin solution in a second solvent to obtain a second slurry.
[0098] In some embodiments, the perfluorosulfonic acid resin solution is a dispersion of perfluorosulfonic acid resin in one or more solvents including water, ethanol, n-propanol or isopropanol, wherein the solid content is 5-30wt%, including but not limited to 10wt%, 15wt% or 20wt%, etc.
[0099] In some embodiments, the second solvent includes a hydroalcoholic solvent (ie, a mixed solvent of water and alcohol).
[0100] Exemplarily, the mass ratio of water to alcohol in the hydroalcohol solvent is 1:(0.5-5), including but not limited to 1:0.5, 1:1, 1:2, 1:4 or 1:5, etc.
[0101] Exemplarily, the alcohol includes, but is not limited to, at least one of ethanol, n-propanol, and isopropanol.
[0102] In some embodiments, the dispersion method of dispersing the hydrogenation reaction catalyst and the perfluorosulfonic acid resin solution in the second solvent includes but is not limited to at least one of ball milling, sand milling or ultrasound.
[0103] In some embodiments, the mass ratio of the hydrogen oxidation reaction catalyst to the perfluorosulfonic acid resin is 1:(0.2-1), including but not limited to 1:0.2, 1:0.3, 1:0.5, 1:0.75 or 1:0.9, etc.
[0104] In some embodiments, the solid content of the second slurry is 1-25 wt %, including but not limited to 5 wt %, 12 wt % or 20 wt %, etc.
[0105] S104, coating the second slurry on the proton storage layer, and then performing a second drying to obtain a proton exchange membrane containing the hydrogen oxidation reaction layer and the proton storage layer.
[0106] In some embodiments, the coating method of coating the second slurry on the proton storage layer includes but is not limited to at least one of blade coating, slit coating, or ultrasonic spray coating.
[0107] In some embodiments, the coating thickness of the second slurry on the proton storage layer by knife coating or slit coating is 10-100 μm, and the spraying speed of ultrasonic spray coating is 0.5-4 mL / min.
[0108] Exemplarily, the wet thickness includes but is not limited to 20 μm, 35 μm or 55 μm, etc., and the spraying speed of ultrasonic spraying includes but is not limited to 1 mL / min, 2 mL / min or 3 mL / min, etc.
[0109] In some embodiments, the second drying temperature is 50-90°C, including but not limited to 55°C, 65°C, 75°C or 85°C.
[0110] It should be noted that, in the method for preparing the membrane electrode of the embodiment of the present application, step S103 may be located before step S101, or between step S101 and step S102.
[0111] <Fuel Cell>
[0112] The fuel cell of the embodiment of the present application includes the membrane electrode of the embodiment of the present application or the membrane electrode prepared by the preparation method of the membrane electrode of the embodiment of the present application.
[0113] In some embodiments, the fuel cell includes but is not limited to a hydrogen fuel cell, and is preferably a hydrogen fuel cell.
[0114] The membrane electrode, the method for preparing the membrane electrode and the fuel cell of the embodiments of the present application all have at least the beneficial effect of the low-cost anti-reverse polarity anode catalyst layer of the embodiments of the present application.
[0115] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0116] 1. Examples and Comparative Examples
[0117] Example 1
[0118] The low-cost anti-reverse polarity anode catalyst layer of this embodiment is composed of a proton storage layer and a hydrogen oxidation reaction layer stacked in sequence. When the proton storage layer is assembled into a membrane electrode, the side away from the hydrogen oxidation reaction layer is in close contact with the proton exchange membrane.
[0119] The method for preparing the membrane electrode comprises the following steps:
[0120] (1) Preparation of WO3 slurry (also known as the first slurry): 1 g of commercially available nano-WO3 with a particle size of less than 200 nm was added to a ball mill, 5 g of a water-alcohol mixture and 0.8 g of a perfluorosulfonic acid resin solution were added, and the mixture was stirred evenly. Ball mill beads were added, and the mixture was ball milled at a speed of 450 rpm for 3 h to obtain a uniformly dispersed WO3 slurry.
[0121] The water-alcohol mixture is a mixed solution of deionized water, anhydrous ethanol and n-propanol in a mass ratio of 1:1:2; the perfluorosulfonic acid resin solution is a dispersion of perfluorosulfonic acid resin with an ion exchange equivalent of 720 g / mol dispersed in solvent deionized water, with a solid content of 25 wt%.
[0122] (2) Coating of proton storage layer: The WO3 slurry prepared in step (1) is scraped onto the surface of the proton exchange membrane with the cathode catalyst layer away from the cathode catalyst layer, and then dried at 60°C to form a proton storage layer with a thickness of 2 μm on the proton exchange membrane.
[0123] The wet thickness of the scraping (i.e. the scraping thickness of the WO3 slurry) is 30 μm; the cathode catalyst layer has a platinum loading of 0.4 mg / cm 2 The platinum-carbon catalyst layer is 8 μm thick; the proton exchange membrane is the G12 membrane produced by Gore Company of the United States, with a thickness of 12 μm.
[0124] (3) Preparation of Pt / C catalyst slurry (also known as the second slurry): 1 g of Pt / C catalyst was added to a ball mill, and 3 g of deionized water was added to fully wet the Pt / C catalyst. Subsequently, 15 g of a water-alcohol mixture and 2 g of a perfluorosulfonic acid resin solution were added, and the mixture was stirred evenly. Ball mill beads were added, and the mixture was ball milled at 450 rpm for 3 h to obtain a uniformly dispersed Pt / C catalyst slurry.
[0125] Among them, the carbon carrier in the Pt / C catalyst is graphitized nano-carbon powder, and the mass ratio of Pt to the carbon carrier is 1:1; the water-alcohol mixed solution is a mixed solution of deionized water, anhydrous ethanol and n-propanol mixed in a mass ratio of 1:1:2; the perfluorosulfonic acid resin solution is a dispersion of perfluorosulfonic acid resin with an ion exchange equivalent of 720 g / mol dispersed in solvent deionized water, and the solid content is 25wt%.
[0126] (4) Preparation of membrane electrode: The Pt / C catalyst slurry obtained in step (3) is scraped onto the surface of the proton storage layer in step (2) away from the proton exchange membrane, and then dried at 60°C to form a hydrogen oxidation reaction layer with a thickness of 2 μm on the proton storage layer to obtain CCM; the frame and gas diffusion layer are then hot pressed to obtain a membrane electrode.
[0127] The wet thickness of the scraping (ie the scraping thickness of the Pt / C catalyst slurry) is 30 μm; the gas diffusion layer is GDL produced by Toray Industries, Japan, with a thickness of 170 μm.
[0128] Example 2 (Compared with Example 1, the transition metal oxide is MoO3)
[0129] This embodiment is basically the same as Embodiment 1, except that:
[0130] In step (1), WO3 is replaced by MoO3.
[0131] Example 3 (Compared with Example 1, the transition metal oxide is a mixture of MoO3 and WO3)
[0132] This embodiment is basically the same as Embodiment 1, except that:
[0133] In step (1), WO3 is replaced by a mixture of MoO3 and WO3 in a mass ratio of 1:1.
[0134] Example 4 (Compared with Example 1, the mass ratio of transition metal oxide to perfluorosulfonic acid resin is 1:1 as the lower limit)
[0135] This embodiment is basically the same as Embodiment 1, except that:
[0136] In step (1), the amount of perfluorosulfonic acid resin solution used is 4 g.
[0137] Example 5 (Compared with Example 1, the mass ratio of transition metal oxide to perfluorosulfonic acid resin is an upper limit of 1:0.1)
[0138] This embodiment is basically the same as Embodiment 1, except that:
[0139] In step (1), the amount of perfluorosulfonic acid resin solution used is 0.4 g.
[0140] Example 6 (Compared with Example 1, the mass ratio of transition metal oxide to Pt / C is 1:3 as the lower limit)
[0141] This embodiment is basically the same as Embodiment 1, except that:
[0142] In step (2), the coating wet thickness is 20 μm.
[0143] Example 7 (Compared with Example 1, the mass ratio of transition metal oxide to Pt / C is 1:1 as the upper limit)
[0144] This embodiment is basically the same as Embodiment 1, except that:
[0145] In step (2), the coating wet thickness is 60 μm.
[0146] Example 8 (Compared with Example 1, the mass ratio of Pt / C to perfluorosulfonic acid resin is 1:1 as the lower limit)
[0147] This embodiment is basically the same as Embodiment 1, except that:
[0148] In step (3), the mass ratio of Pt to carbon carrier in the Pt / C catalyst is 1:4, the amount of perfluorosulfonic acid resin solution is 4 g, the mass of the water-alcohol mixture is 13 g, and the wet coating thickness is 80 μm.
[0149] Example 9 (Compared with Example 1, the mass ratio of Pt / C to perfluorosulfonic acid resin is an upper limit of 1:0.2)
[0150] This embodiment is basically the same as Embodiment 1, except that:
[0151] In step (3), the mass ratio of Pt to carbon carrier in the Pt / C catalyst is 3:2, the amount of perfluorosulfonic acid resin solution is 0.8 g, the mass of the water-alcohol mixture is 16.2 g, and the wet coating thickness is 25 μm.
[0152] Example 10 (Compared with Example 1, Pt in Pt / C is replaced by Pt alloy)
[0153] This embodiment is basically the same as Embodiment 1, except that:
[0154] In step (3), the Pt in the Pt / C catalyst is replaced with an alloy of Pt and Co, and the mass ratio of Pt to Co is 9:1.
[0155] Comparative Example 1
[0156] This comparative example is basically the same as Example 1, except that:
[0157] This comparative example is a conventional anode catalyst layer, which is composed of a Pt / C catalyst and a perfluorosulfonic acid resin.
[0158] The preparation method of the membrane electrode does not include step (1) and step (2). In step (4), the Pt / C catalyst slurry is directly scraped onto the surface of the proton exchange membrane with the cathode catalyst layer away from the cathode catalyst layer to obtain the CCM.
[0159] The coating thickness is 30 μm; the cathode catalyst layer has a platinum loading of 0.4 mg / cm 2 The platinum-carbon catalyst layer is 8 μm thick; the proton exchange membrane is the G12 membrane produced by Gore Company of the United States, with a thickness of 12 μm.
[0160] Comparative Example 2
[0161] This comparative example is basically the same as Example 1, except that:
[0162] When assembling into a membrane electrode, the positions of the proton storage layer and the hydrogen oxidation reaction layer are swapped. That is, although the anode catalyst layer is also composed of a proton storage layer and a hydrogen oxidation reaction layer, the hydrogen oxidation reaction layer is close to the proton exchange membrane on the side away from the proton storage layer.
[0163] The method for preparing a membrane electrode comprises the following steps:
[0164] (1) Preparation of Pt / C catalyst slurry (also known as the second slurry): 1 g of Pt / C catalyst was added to a ball mill, and 3 g of deionized water was added to fully wet the Pt / C catalyst. Subsequently, 15 g of a water-alcohol mixture and 2 g of a perfluorosulfonic acid resin solution were added, and the mixture was stirred evenly. Ball mill beads were added, and the mixture was ball milled at 450 rpm for 3 h to obtain a uniformly dispersed Pt / C catalyst slurry.
[0165] The carbon carrier in the Pt / C catalyst is graphitized nano-carbon powder, and the mass ratio of Pt to the carbon carrier is 1:1; the water-alcohol mixed solution is a mixed solution of deionized water, anhydrous ethanol and n-propanol in a mass ratio of 1:1:2; the perfluorosulfonic acid resin solution is a dispersion of perfluorosulfonic acid resin with an ion exchange equivalent of 720 g / mol dispersed in solvent water, and the solid content is 25wt%. (2) Hydrogen oxidative reaction layer coating: The Pt / C catalyst slurry prepared in step (1) is scraped onto the surface of the proton exchange membrane with a cathode catalyst layer away from the cathode catalyst layer, and then dried at 60°C to form a hydrogen oxidative reaction layer with a thickness of 2 μm on the proton exchange membrane.
[0166] The coating thickness is 30 μm; the cathode catalyst layer has a platinum loading of 0.4 mg / cm 2 The platinum-carbon catalyst layer is 8 μm thick; the proton exchange membrane is the G12 membrane produced by Gore Company of the United States, with a thickness of 12 μm.
[0167] (3) Preparation of WO3 slurry (also known as the first slurry): Take 1g of nano-WO3 with a particle size of less than 200nm and add it to a ball mill. Add 5g of a water-alcohol mixture and 0.8g of a perfluorosulfonic acid resin solution, stir evenly, add ball mill beads, and ball mill at 450rpm for 3h to obtain a uniformly dispersed WO3 slurry.
[0168] The water-alcohol mixture is a mixed solution of deionized water, anhydrous ethanol and n-propanol in a mass ratio of 1:1:2; the perfluorosulfonic acid resin solution is a dispersion of perfluorosulfonic acid resin with an ion exchange equivalent of 720 g / mol dispersed in solvent water, with a solid content of 25 wt%.
[0169] (4) Preparation of membrane electrode: The WO3 slurry obtained in step (3) is scraped onto the surface of the hydrogen oxidation reaction layer in step (2) away from the proton exchange membrane, and then dried at 60°C to obtain CCM; the frame and gas diffusion layer are then hot pressed to obtain a membrane electrode.
[0170] Among them, the scraping thickness is 30μm; the gas diffusion layer is GDL from Japan Toray Company, with a thickness of 170μm.
[0171] Comparative Example 3 (all raw materials are mixed into slurry, and then coated on the proton exchange membrane)
[0172] The anode catalyst layer of this comparative example is composed of Pt / C catalyst, nano WO3 and perfluorosulfonic acid resin.
[0173] The preparation method of this comparative example comprises the following steps:
[0174] (1) Slurry preparation: 0.5 g of nano-WO3, 1 g of Pt / C catalyst and 2.8 g of perfluorosulfonic acid resin solution were added to a ball mill, and then 15 g of water-alcohol solution was added. The mixture was stirred evenly, and ball mill beads were added. The mixture was ball milled at 450 rpm for 3 h to obtain a uniformly dispersed slurry.
[0175] (2) Preparation of membrane electrode: The slurry obtained in step (1) is scraped onto the surface of the proton exchange membrane with the cathode catalyst layer away from the cathode catalyst layer, and then dried at 60°C to obtain CCM; and then the frame and gas diffusion layer are hot pressed to obtain a membrane electrode.
[0176] The rest are the same as in Example 1.
[0177] 2. Performance Test
[0178] 1. The anode catalyst layer in the membrane electrode prepared in each embodiment and comparative example (for the embodiment, a composite material layer of a proton storage layer and a hydrogen oxidation reaction layer arranged in sequence on a proton exchange membrane) was tested by an X-ray fluorescence spectrometer (XRF) to analyze the loading of active substances and transition metal oxides in the anode catalyst layer. The results are shown in Table 1.
[0179] Table 1 XRF test results of the anode catalyst layer in the membrane electrode prepared in each embodiment and comparative example
[0180]
[0181] It can be seen from Table 1 that the loading of the membrane electrode anode catalyst layer prepared in the embodiment and the comparative example is within the design range, indicating that the preparation methods of the embodiment and the comparative example of the present invention are both very feasible.
[0182] 2. The membrane electrodes prepared in each embodiment or comparative example were assembled into a single cell, and polarization performance tests and anti-reverse polarity time tests were performed.
[0183] The assembly method of a single cell is: assemble in the order of anode end plate, anode current collector plate, anode flow field plate, anode gasket, membrane electrode, cathode gasket, cathode flow field plate, cathode current collector plate, and cathode end plate, and fasten the end plates on both sides with screws and bolts to assemble into a single cell. Among them, the active area of the membrane electrode catalyst layer is 5cm×5cm, and the flow channel of the flow field plate is a parallel flow channel. The components and assembly methods of the single cell refer to the national standard "GB / T 28817-2022 / IEC / TS 62282-7-1:2017 Polymer Electrolyte Fuel Cell Single Cell Test Method".
[0184] The test method for polarization performance is: the temperature of the fuel cell (i.e. the above-mentioned single cell) is 80°C; hydrogen and air are introduced into the anode and cathode respectively, the pressures of hydrogen and air are 100kPa and 90kPa respectively, the excess coefficients are 1.5 and 2.0 respectively, and the humidity is 50% and 40% respectively.
[0185] The test method for the anti-reverse polarity time is as follows: the fuel cell temperature is 65°C; nitrogen and air are introduced into the anode and cathode respectively, the flow rates of nitrogen and air are 0.4L / min and 0.8L / min respectively, the humidity is 70% and 70%, and the current density is 0.2A / cm 2 .
[0186] Test results such as Figure 3 , Figure 4 , as shown in Table 2 and Table 3.
[0187] Figure 3 The polarization curves of the membrane electrodes prepared in Example 1 and Comparative Examples 1-3 are shown in FIG. Figure 3 It can be seen that Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 have a 2A / cm 2 The voltage is between 0.663V and 0.673V, and the difference is within 10mV, so the performance is considered to be similar. This indicates that the anode catalyst layer is constructed as a double-layer structure, and the distribution position of the double-layer structure has no obvious effect on the membrane electrode polarization performance.
[0188] Table 2 Polarization curve performance of each embodiment and comparative example
[0189] Example / Comparative Example <![CDATA[Polarization performance (V @ 2 A / cm 2 )]]> Example 1 0.670 Comparative Example 1 0.668 Comparative Example 2 0.663 Comparative Example 3 0.673
[0190] Figure 4 The voltage curves of the membrane electrodes prepared in Example 1 and Comparative Examples 1-3 when lacking hydrogen. The membrane electrode anti-reverse polarity time is defined as the time it takes for the voltage to drop from 0V to -1.5V. Figure 4 It can be seen from the test results that the time taken for the voltage of Example 1 to decrease from 0V to -1.5V is the longest, indicating that when the anode lacks hydrogen, H x WO3 can decompose to produce protons and electrons to maintain voltage balance, and H xWO3 is closer to the proton exchange membrane and is more likely to transfer the protons generated by decomposition to the cathode. Therefore, the membrane electrode of Example 1 has the best anti-reverse polarity performance. The time for the membrane electrode voltage of Comparative Example 2 to drop from 0V to -1.5V is also the shortest, indicating that the order of the proton storage layer and the hydrogen oxidation reaction layer cannot be changed when the low-cost anti-reverse polarity anode catalyst layer of the embodiment of the present application is assembled into a membrane electrode.
[0191] Table 3 Test results of membrane electrode anti-reverse polarity time of each embodiment and comparative example
[0192]
[0193]
[0194] It can be seen from Table 3 that the anti-reverse polarity time of Example 1 is the longest, reaching 47 seconds. During the operation of the fuel cell system, the system's voltage inspection can identify the occurrence of reverse polarity within this time and adjust the operating conditions in time to avoid carbon corrosion reactions that affect the life of the fuel cell system.
[0195] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0196] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0197] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A low-cost anti-reverse polarity anode catalyst layer, characterized in that: It comprises a proton storage layer and a hydrogen oxidation reaction layer which are stacked, wherein the proton storage layer comprises a transition metal oxide and a perfluorosulfonic acid resin, wherein the transition metal oxide comprises at least one of WO3 and MoO3, and the hydrogen oxidation reaction layer comprises a hydrogen oxidation reaction catalyst and the perfluorosulfonic acid resin.
2. The low-cost anti-reverse polarity anode catalyst layer according to claim 1, characterized in that: The transition metal oxide is WO3 or MoO3.
3. The low-cost anti-reverse polarity anode catalyst layer according to claim 1, characterized in that: In the proton storage layer, the mass ratio of the transition metal oxide to the perfluorosulfonic acid resin is 1:(0.1-1).
4. The low-cost anti-reverse polarity anode catalyst layer according to claim 1, characterized in that: In the hydrogen oxidation reaction layer, the mass ratio of the hydrogen oxidation reaction catalyst to the perfluorosulfonic acid resin is 1:(0.2-1).
5. The low-cost anti-reverse polarity anode catalyst layer according to claim 1, characterized in that: The mass ratio of the proton storage layer to the hydrogen oxidation reaction layer is 1:(1-5); and / or, The thickness of the proton storage layer is 0.5-4 μm; and / or, The thickness of the hydrogen oxidation reaction layer is 1-10 μm; and / or, The transition metal oxide is a nanoparticle; and / or, The particle size of the transition metal oxide is less than 200 nm; The ion exchange equivalent of the perfluorosulfonic acid resin is 700-1100 g / mol.
6. The low-cost anti-reverse polarity anode catalyst layer according to claim 1, characterized in that: The hydrogen oxidation reaction catalyst includes an active substance and a carbon carrier, the active substance includes Pt or a Pt alloy, and / or the carbon carrier includes at least one of graphitized nano-carbon powder, carbon nanotubes, carbon nanofibers and graphene, and / or the mass ratio of the active substance to the carbon carrier is 1:(0.5-4).
7. A membrane electrode, comprising a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer, characterized in that: The anode catalyst layer is a low-cost anti-reverse polarity anode catalyst layer as claimed in any one of claims 1 to 6, and the proton storage layer is arranged on the proton exchange membrane away from the hydrogen oxidation reaction layer.
8. A method for preparing a membrane electrode as claimed in claim 7, characterized in that: include: Dispersing the transition metal oxide and the perfluorosulfonic acid resin solution in a first solvent to obtain a first slurry; Applying the first slurry on a proton exchange membrane, followed by a first drying step to obtain a proton exchange membrane containing the proton storage layer; dispersing the hydrogenation reaction catalyst and the perfluorosulfonic acid resin solution in a second solvent to obtain a second slurry; The second slurry is coated on the proton storage layer, followed by a second drying process, to obtain a proton exchange membrane including the hydrogen oxidation reaction layer and the proton storage layer.
9. The preparation method according to claim 8, characterized in that: The first solvent and the second solvent both include hydroalcoholic solvents, wherein the alcohol in the hydroalcoholic solvent includes at least one of ethanol, n-propanol and isopropanol; and / or, In the process of obtaining the first slurry and the process of obtaining the second slurry, the dispersion method includes at least one of ball milling, sand milling or ultrasound; and / or, The coating method of coating the first slurry on the proton exchange membrane and the coating method of coating the second slurry on the proton storage layer both include blade coating, slit coating or ultrasonic spray coating; and / or, The temperatures of the first drying and the second drying are both 50-90°C.
10. A fuel cell, characterized in that: It comprises the membrane electrode as claimed in claim 7 or the membrane electrode prepared by the preparation method as claimed in claim 8 or 9.